Natural Topical Treatment Contributes to a Reduction of Dry Scalp Symptoms in Children - Fithian E; Thivalapill N; Kosner J; Necheles J; Bilaver L (Dove Medical Press, 2023)
Eirene Fithian,1 Neil Thivalapill,1 John Kosner,1 Jonathan Necheles,2 Lucy Bilaver1 1Center for Food Allergy and Asthma Research, Northwestern University Feinberg School of Medicine, Chicago, IL, USA; 2Children's Healthcare Associates, Chicago, IL, USACorrespondence: Lucy Bilaver, Center for Food Allergy and Asthma Research, Northwestern University Feinberg School of Medicine, 750 N. Lake Shore Drive, 6th Floor, Chicago, IL, 60611, USA, Tel +1 312-503-5618, Email l-bilaver@northwestern.eduBackground: Dry scalp conditions affect a significant portion of the population, including children. Emerging evidence indicates the potential for improvement of atopic symptoms through altering the skin microbiome. Therefore, a topical treatment consisting of probiotic extracts, honey, turmeric, and vitamin B12 was manufactured to improve dry scalp symptomology through sustained balance of the microbiome.Purpose: This interventional clinical study aims to determine the safety and efficacy of the topical treatment in reducing dry scalp symptomology in children 1- 17 years old with dry scalp symptoms.Methods: Participants applied the topical dry scalp treatment 2- 3 times per week for two weeks. Safety and efficacy of the topical treatment was determined through physician assessment using the validated Investigator's Global Assessment (IGA) scale and the Total Severity Scale (TSS) during pre- and post-treatment clinic visits as well as parent reports at baseline, 1-week midpoint, and 2-week exit.Results: Use of the topical treatment was associated with reduced symptoms of itchiness, dryness, irritation, and flakiness in children. The average IGA score was 3.0 at baseline and 2.0 after treatment, corresponding to a score difference of 1.0 (p < 0.001, 95% CI: 0.7, 1.2). The TSS score difference was 1.9 (p < 0.001, 95% CI: 1.4, 2.4). The total parent-reported scalp severity score decreased from 16.6 (95% CI: 14.8, 18.4) to 12.4 (p < 0.001, 95% CI: 11.0, 13.7) at 2-week exit.Discussion: Study results mirror those reported in a study conducted in adults and point to the safety and efficacy of this natural topical treatment in reducing dry scalp symptomology in children. Based on our data, the combination of probiotic extracts and other anti-inflammatory ingredients appears to improve overall scalp health and appearance, though further studies will need to be conducted to further elucidate the link between clinical improvement and a balanced scalp microbiome.Keywords: dry scalp, dandruff, seborrheic dermatitis, atopic disease, microbiome, probiotic